The value of international assignments through the lens of real-options-reasoning - Renshaw, Phil St John; Dickmann, Michael; Parry, Emma (Elsevier, 2021)
Studies over several decades demonstrate that international assignments (IAs) are implemented for a variety of reasons and yet their total organizational value is generally not assessed nor theoretically understood. We suggest that a new theoretical approach is needed in order to understand the organizational value of IAs more fully. Using data from the financial services sector we apply real options theory to IAs and identify two organizational real options – for the home and host respectively. We argue that real-options-reasoning offers theoretical clarity to understanding the organizational value of IAs. This paper identifies new practical consequences for managers to maximize the value of their IAs and a series of research propositions to extend our comprehension of IA managerial decision-making.
Keywords: Expatriation; Organizational value; Real-options-reasoning